Notas de la agricultura al final del antiguo régimen en un pueblo de la montaña leonesa, Las Bodas (Boñar), 1750-1840 - González García, José María (Estudios humanísticos. Geografía, historia y arte, 2021)
«Notes on the agriculture at the end of the ancient regime in a village in the mid mountain in the province of León. Las Bodas (Boñar) 1750-1840». The general features of the agricultural activity in the transitional period to the liberalism are analysed: the superiority of the crops of grain, the solid dividing of the ground of agricultural use, the existence of small property and the importance of the agricultura! heritage of the church. The agricultural production, according to church documents, will increase at the end of the XVIII century and the beginning of the XIX c, with some bad harvest years, which will be reflected in the evolution of prices